Penerapan PERMA No.1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan Agama Badung dalam Pencabutan Perkara Cerai Talak - I Gede Satya Bala Putra Dewa; I Nyoman Putu Budiartha; A.A Sagung Laksmi Dewi (Fakultas Hukum Universitas Warmadewa, 2019)
Rules of the Supreme Court or PERMA is basically a form of regulation which contains provisions of a legal nature of the event. In relation to rule on divorce, I need to know the difference between a PERMA No.1 Year 2016 with PERMA No.1 Year 2008 about mediation. namely, regarding the time limit shorter again 10 days earlier than the deadline for mediation 40 days now becomes 30 days in the count when the existence of the assignment orders for mediation. Both the parties are required to attend the mediation meeting immediately on the use of